Design Virtual Tour Technology Application to Improve Digital Literacy of Teachers and Students About Edu-tourism - Maryanto; Buchori, Achmad; Zhannisa, Utvi Hinda; Wibisana, Muh Isna Nurdin (Universitas Pendidikan Ganesha, 2024)
More technological innovation in the tourism sector must be integrated with educational aspects and digital literacy, especially during a pandemic that limits physical visits to tourist attractions. Although several tourism applications have been developed, only a few have been specifically designed to improve digital literacy and visitor knowledge in terms of educational content and integration with the school curriculum. This research aims to create a virtual tour-based edu-tourism application that is packaged with virtual reality applications. This research is a research and development using the ADDIE model. The subjects of this research were randomly 250 teachers and high school / vocational school students. The data collection method was a questionnaire using an instrument in the form of an instrument sheet. After the data was collected, it was analyzed using quantitative and qualitative descriptive data analysis methods. The results showed that the design of the virtual tour technology application received a very good assessment in the aspects of media, material, discussion, and display. This is also in line with the teacher's response, which assessed these aspects positively, with the highest score given to the media aspect, followed by the material, discussion, and display. This study concludes that the virtual tour-based eduwisata application packaged with virtual reality applications is effective in improving the literacy skills of teachers and students regarding eduwisata. The results of this study indicate that virtual tour applications can be implemented as interactive learning media that can improve student and teacher literacy in the field of edu-tourism.